ANALISIS ASPEK-ASPEK YANG MEMPENGARUHI PEMANFAATAN AIR IRIGASI DAN HUBUNGANNYA TERHADAP KELAYAKAN USAHATANI PADI SAWAH - Agustin Kuadi; Asda Rauf; Amir Halid (Universitas Negeri Gorontalo, 2017)
This research aims at 1) investigating the aspects that influence irrigation water utilization in Village of Toluwaya, Sub-district of Bulango Timur, District of Bone Bolango; 2) investigating ricefield paddy farm appropriateness in utilization of irrigation water in Village of Toluwaya, Sub-district of Bulango Timur, District of Bone Bolango. This research applies survey method. It was conducted from October to November 2016. Data of the research are analyzed descriptively and farm appropriateness. Samples of the research are 23 respondents that are taken by slovin method. Research findings are: 1) the aspects that influence irrigation water utilization, influence and related to business appropriateness where the appropriateness is above IDR. 3.41, thus every 1 rupiah of expenditure will obtain profit. This is influenced by supporting facility for irrigation such as aspect of irrigation maintenance, irrigation repair and irrigation management. Irrigation water utilization is in good category with average score of 13.73 with percentage of 59.70%. Then, farm appropriateness is IDR. 3.41. 2) the total cost paid by farmers during the farming process is IDR. 7.441.956 with reception of IDR.25.326.087. Thus, the income is IDR. 17.884.131. Therefore, this farm is proper to be developed as value of R/C ratio is3,41 or 1. This means that every 1 rupiah of expenditure will give reception of 3,41.